Fatigue – an underestimated symptom in psoriatic arthritis - Magdalena Krajewska-Włodarczyk; Agnieszka Owczarczyk-Saczonek; Waldemar Placek (Rheumatology, 2017)
The nature of fatigue is very complex and involves physiological, psychological and social phenomena at the same time, and the mechanisms leading to occurrence and severity of fatigue are still poorly understood. The condition of chronic inflammation associated with psoriatic arthritis can be regarded as a potential factor affecting development of fatigue. Only a few studies so far have focused on the occurrence of fatigue in psoriatic arthritis. The problem of chronic fatigue is underestimated in everyday clinical practice. Identification and analysis of subjective fatigue components in each patient can provide an objective basis for optimal fatigue treatment in daily practice. This review presents a definition of chronic fatigue and describes mechanisms that may be associated with development of fatigue, highlighting the role of chronic inflammation, selected fatigue measurement methods and relations of fatigue occurrence with clinical aspects of psoriatic arthritis.